1995
DOI: 10.1097/00006676-199507000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Lymphocyte Subsets in Human Acute Pancreatitis

Abstract: We investigated peripheral lymphocyte subsets in 34 consecutive acute pancreatitis patients (21 males, 13 females; mean age, 57 years; range, 16-85 years) studied within 48 h of pain onset and for 5 consecutive days to understand better the immunological response during the course of the disease. The diagnosis was based on characteristic abdominal pain associated with a twofold increase in serum lipase and confirmed by imaging techniques in all patients. Acute pancreatitis was of biliary origin in 25 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 12 publications
2
31
0
1
Order By: Relevance
“…In contrast, the lymphocytic immune response occurs later and its main function is to mediate and resolve the preceding nonspecific inflammatory process. Prior studies have shown an association between lower peripheral lymphocyte counts and the severity of cases of acute pancreatitis [31,32,33]. Such decline in lymphocyte count in acute pancreatitis was attributed to apoptosis and was also associated with lymphocyte dysfunction [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the lymphocytic immune response occurs later and its main function is to mediate and resolve the preceding nonspecific inflammatory process. Prior studies have shown an association between lower peripheral lymphocyte counts and the severity of cases of acute pancreatitis [31,32,33]. Such decline in lymphocyte count in acute pancreatitis was attributed to apoptosis and was also associated with lymphocyte dysfunction [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Immunological impairment in the early phase may be linked to increased susceptibility to subsequent infection and the development of septic complications. Several investigators have reported the reduction in peripheral lymphocyte count, [4][5][6] and it may reflect the immunological impairment. Particularly, Curley et al reported a significant decrease in the proportion of helper T cells in severe acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Immunologic impairment in the early phase may be linked to the increased susceptibility to subsequent infection and the development of septic complications. Several investigators have reported a reduction of the peripheral lymphocyte count in acute pancreatitis, [3][4][5][6][7] which may indicate immunologic impairment. Curley et al 4 reported a significant decrease in the proportion of CD4-positive lymphocytes (T-helper cells) in SAP.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have demonstrated a significant decrease in CD4-and CD8-positive lymphocytes in SAP. [5][6][7] However, the relationship between lymphocyte reduction and subsequent infection has not been investigated.…”
Section: Introductionmentioning
confidence: 99%